2021
DOI: 10.3390/rs13030532
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Comparing Shading Effects of 3D Tree Structures with Virtual Leaves

Abstract: Reduced solar radiation brought about by trees on agricultural land can both positively and negatively affect crop growth. For a better understanding of this issue, we aim for an improved simulation of the shade cast by trees in agroforestry systems and a precise estimation of insolation reduction. We present a leaf creation algorithm to generate realistic leaves to be placed upon quantitative structure models (QSMs) of real trees. Further, we couple it with an enhanced approach of a 3D model capable of quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 59 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…The minimum spanning tree (MST) between the Delaunay triangulation edges of point clouds was found [49,50]. The length of edge defined in Euclidean space weighted all edges.…”
Section: Enable Adqsm To Automatically Rebuild Tree Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The minimum spanning tree (MST) between the Delaunay triangulation edges of point clouds was found [49,50]. The length of edge defined in Euclidean space weighted all edges.…”
Section: Enable Adqsm To Automatically Rebuild Tree Structurementioning
confidence: 99%
“…To test the accuracy of QSM method in estimating trunk volume from TP point clouds, we compared reconstructed trunk volume values of AdQSM and TreeQSM with reference trunk volume of the allometric equation respectively, Figure 14 Figure 16 [40,41]. At present, AdQSM has attracted more and more people's attention [50][51][52][53]. AdQSM needs to be tested using photogrammetric point clouds.…”
Section: Trunk Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TLS derived point clouds coupled with QSMs have been used for modelling the shade cast at fine spatiotemporal resolutions, thus improving the understanding of the role of trees as physical light obstacles. Initial works by Rosskopf et al (2017), Bohn Reckziegel et al (2021, have demonstrated the potential of applying these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The innovation of our research lies within the application of these analogous tree structures, for creating shading scenarios, and by doing so, supporting the design and choice of adequate tending operations. Pruned and unpruned tree structures are fed into a shadow model (Bohn Reckziegel et al 2021) with a fine spatiotemporal resolution, to simulate the shade cast over twelve months and to estimate the insolation reduction on the ground as a result. We hypothesise that conventional and selective pruning methods with comparable branch volume removal differ markedly in both retained tree structures and the shading effects.…”
Section: Introductionmentioning
confidence: 99%